Creating and Utilizing UGC Through Social Media in Trip Planning - Helga Liliani Cakra Dewi (Ikatan Sarjana Komunikasi Indonesia, 2018)
This study aims to understand the behavior of social media users in creating and utilizing User Generated Content (UGC) in trip planning (before, during, and after the trip), and to inform which social media that mostly used by users. Through understanding the behavior of social media users in creating and utilizing UGC, this research is expected to contribute to the tourism organization in formulating promotion strategies in social media effectively. A survey is conducted to collect research data from 180 of communication students. This research found that Instagram (used by 96.7% of respondent) and Kaskus (used by 6.7% of respondent) have significant influence towards users in utilizing and creating the UGC in trip planning.